Cárcel : un punto de llegada y, en ocasiones, un punto de partida - Rayes, Astrid Flavia (2017)
La elaboración del presente trabajo apunta a indagar sobre los encuentros y desencuentros entre el derecho y la Psicología en la compleja tarea de administración de justicia. ¿Por qué debería interesarnos esa función siendo psicólogos? ¿De qué ley hablamos cuando hablamos los psicólogos? Sin tener respuestas taxativas respecto de estos interrogantes puedo inferir, a partir de lo que Sigmund Freud (1932) plantea, que la posibilidad del lazo social y, por lo tanto, de la vida en comunidad, está vinculada a la identificación con la ley (alguna ley) constituyendo vínculos de alianza y que la administración de justicia permite de algún modo sostener una excusa para regular la pulsión. (Resumen parcial)
The elaboration of the present work aims to investigate the encounters and disagreements between Law and Psychology in the complex task of Administration of Justice. Why should we be interested in that role as psychologists? What law do we speak when we speak psychologists? Without any definite answers to these questions, I can infer from Sigmund Freud (1932) that the possibility of the social bond, and therefore of community life, is linked to identification with the law (some law) Forming alliance bonds; And that the administration of justice somehow allows an excuse to regulate the drive. In order to investigate whether or not it occurs, and in what way a subjective effect on the offender, from the legal penalty, I will address a case. I will consider from the same concepts as violent emotion / passage to the act, Imputability / subjective responsibility. Concepts belonging to different disciplinary fields and therefore representative of the crossing of speeches in Forensic Psychology.
Keywords: Justicia; Cárcel; Imputabilidad; Pasaje al acto; Justice; Jail; Imputability; Passage to the act